2016
DOI: 10.1515/dmpt-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Medication therapy management (MTM): an innovative approach to improve medication adherence in diabetics

Abstract: Medication adherence is a key component of self-management for patients with diabetes. A pharmacist-led MTM programme if appropriately designed and implemented will have a potential positive impact on medication adherence in diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…A similar study conducted in a diabetic outpatient clinic in Jordan assessing self-reported medication adherence 6 months following intervention, revealed a higher proportion of adherent patients in the intervention group (71%), which was also significantly higher than that in the usual care control group (35%). [25] Another prospective interventional study conducted by Murali et al [26] over a 1-year period for diabetic patients showed very low adherence level to antidiabetic medications before intervention. Murali et al [26] showed that 24% of the patients became highly adherent and 68% reached medium adherence reflecting on the positive role of the pharmacist and the value of the MMR service.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A similar study conducted in a diabetic outpatient clinic in Jordan assessing self-reported medication adherence 6 months following intervention, revealed a higher proportion of adherent patients in the intervention group (71%), which was also significantly higher than that in the usual care control group (35%). [25] Another prospective interventional study conducted by Murali et al [26] over a 1-year period for diabetic patients showed very low adherence level to antidiabetic medications before intervention. Murali et al [26] showed that 24% of the patients became highly adherent and 68% reached medium adherence reflecting on the positive role of the pharmacist and the value of the MMR service.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Another prospective interventional study conducted by Murali et al [26] over a 1-year period for diabetic patients showed very low adherence level to antidiabetic medications before intervention. Murali et al [26] showed that 24% of the patients became highly adherent and 68% reached medium adherence reflecting on the positive role of the pharmacist and the value of the MMR service. A prospective randomised controlled trial assessed the impact of pharmacist-managed clinic (similar to the HMMR service) on medication adherence in COPD patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations